AKSELERASI INOVASI TEKNOLOGI SPESIFIK LOKASI STRATEGI PENINGKATAN PRODUKSI DI MASA PANDEMI COVID-19 - Roosganda Elizabeth (Universitas Galuh Ciamis, 2021)
Food is the most basic and foremost human need, whose adequacy and quality determine the level of intelligence and quality of human resources. One of the important and strategic aspects of agriculture can be seen from the national/regional contribution (GDP/GDPR). Agriculture remains the main priority for development policies in Indonesia, especially during the Covid 19 pandemic, which is still endemic today. This paper, which is a review of various information data and related literature, aims to present various levels of technology application, levels of technical efficiency in various agro-ecosystems, which are presented in a qualitative deductive manner. The occurrence of the global financial crisis (for the short term) and climate change (for the long term) as well as national disasters (for example the Covid 19 pandemic) resulted in a weakening of the economy, especially its growth, increased unemployment, and decreased purchasing power. This condition causes access to food to decline, so that food security is predicted to be more vulnerable. It is necessary to provide technology and information according to needs, adequate government and operational policy tools, the functioning of various supporting institutions (research, extension, marketing) that are more focused and take sides in accelerating the achievement of location-specific technological innovations. This is the right strategy for fulfilling national food. Evaluation of agricultural development policies from the aspect of food institutions is needed as a strategy and measures for the accuracy of policy formulation in supporting future increases in national rice production.